2005
DOI: 10.1086/430527
|View full text |Cite
|
Sign up to set email alerts
|

Re‐creating Ancient Hybrid Species’ Complex Phenotypes from Early‐Generation Synthetic Hybrids: Three Examples Using Wild Sunflowers

Abstract: Can the complex phenotypes that characterize naturally occurring hybrid species be re-created in early-generation artificial hybrids? We address this question with three homoploid hybrid species (Helianthus anomalus, Helianthus deserticola, Helianthus paradoxus) and their ancestral parents (Helianthus annuus, Helianthus petiolaris) that are phenotypically distinct and ecologically differentiated. These species, and two synthetic hybrid populations of the ancestral parents, were characterized for morphological,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 70 publications
2
35
0
Order By: Relevance
“…S. squalidus was also distinct from Sicilian hybrids on the basis of six QTs, including the three transgressive traits (Table 2). These findings are in accordance with observations of other homoploid hybrid species, such as H. anomalus and H. deserticola, which showed that the hybrid species were distinct from earlygeneration hybrids and exhibit particular QTs that are transgressive relative to their parents H. annuus and H. petiolaris (Schwarzbach et al, 2001;Rosenthal et al, 2002Rosenthal et al, , 2005. Transgressive QT expression can be spontaneously generated in new hybrids when QTLs with fixed but opposing directions of effects within species segregate in heterozygous hybrids and also by interaction of divergent gene expression mechanisms in hybrids (Rieseberg et al, 1999;Hegarty and Hiscock, 2008).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…S. squalidus was also distinct from Sicilian hybrids on the basis of six QTs, including the three transgressive traits (Table 2). These findings are in accordance with observations of other homoploid hybrid species, such as H. anomalus and H. deserticola, which showed that the hybrid species were distinct from earlygeneration hybrids and exhibit particular QTs that are transgressive relative to their parents H. annuus and H. petiolaris (Schwarzbach et al, 2001;Rosenthal et al, 2002Rosenthal et al, , 2005. Transgressive QT expression can be spontaneously generated in new hybrids when QTLs with fixed but opposing directions of effects within species segregate in heterozygous hybrids and also by interaction of divergent gene expression mechanisms in hybrids (Rieseberg et al, 1999;Hegarty and Hiscock, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…However, the population sampling approach of our study does not permit adequate partitioning of genetic and environmental contributions to quantitative variance, preventing Q st estimates that, validly, can be directly compared with molecular genetic estimates. Therefore, we chose instead to focus on multivariate analysis of QTs that have been successfully applied in other hybrid studies (for example, Brochmann et al, 2000;Rosenthal et al, 2002Rosenthal et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…The active dune habitat of H. anomalus has higher water availability and lower N than the adjacent stabilized dune habitats of H. deserticola (Rosenthal et al 2005a). Phenologically, H. anomalus generally Xowers and sets seed later than H. deserticola , Rosenthal et al 2005b. Previous comparisons of leaf ecophysiological traits in greenhouse studies and Weld experimental gardens have demonstrated that H. anomalus is always more succulent and tends to have larger leaves with lower N concentration, but that the species do not consistently diVer in WUE (Schwarzbach et al 2001;Rosenthal et al 2002;Rieseberg et al 2003;Brouillette et al 2006).…”
Section: Study Species and Populationsmentioning
confidence: 99%
“…Because this type of speciation appears to occur rapidly (Ungerer et al 1998), it is sometimes possible to experimentally replicate the early stages of the hybrid speciation process. Comparison of experimental hybrid lineages with those that originated naturally has provided a powerful means for reconstructing the speciation process (Rieseberg et al 1996a;Lexer et al 2003;Gross et al 2004;Ludwig et al 2004;Gross and Rieseberg 2005;Hegarty and Hiscock 2005;Rosenthal et al 2005).Three of the best-investigated examples of homoploid hybrid species are annual sunflowers. Molecular evidence indicates that independent hybridization events between the annual sunflowers Helianthus annuus and Helianthus petiolaris, both widespread throughout North America, gave rise to three hybrid species, Helianthus anomalus, Helianthus deserticola, and Helianthus paradoxus (Rieseberg 1991), all with restricted geographical distributions in the southwestern United States.…”
mentioning
confidence: 99%
“…Because this type of speciation appears to occur rapidly (Ungerer et al 1998), it is sometimes possible to experimentally replicate the early stages of the hybrid speciation process. Comparison of experimental hybrid lineages with those that originated naturally has provided a powerful means for reconstructing the speciation process (Rieseberg et al 1996a;Lexer et al 2003;Gross et al 2004;Ludwig et al 2004;Gross and Rieseberg 2005;Hegarty and Hiscock 2005;Rosenthal et al 2005).…”
mentioning
confidence: 99%